(untitled) (Nigerian Journal of Technology, 2017)
Kaolin samples from Ajebo and Darazo in Nigeria were characterized and used to produce zeolite-A crystals. The thermal analysis indicates that both samples undergo de-hydroxylation from 450 oC to about 700 oC and are converted to metakaolin with a weight loss of about 11.39 and 10.43% for the Ajebo and Darazo samples respectively. Characteristic OH, Al-OH, Si-OH and Si-O-Al bands were confirmed in both samples with Infra-red spectroscopy studies. The X-ray diffraction patterns clearly show the presence of the characteristic peaks (12.35 and 24.88o) of kaolinite with little quartz impurities. X-ray diffraction measurements (2? peaks at 7–18o and 21–35o) and scanning electron micrographs clearly show that zeolite-A crystals are produced. The microstructures of kaolin, metakaolin and zeolite-A crystals reveal the presence of platy crystals, amorphous spherical aggregates and cubic-shaped crystals with some amorphous gel respectively. The results show that both Ajebo and Darazo kaolin are suitable for zeolite-A synthesis. http://dx.doi.org/10.4314/njt.v37i1.12